PERENCANAAN MODEL BISNIS PADA START-UP “FEME.ID” MENGGUNAKAN METODE BUSINESS MODEL CANVAS (BMC) - Siti Muflikhatun; Retno Waluyo (JURNAL REKAYASA INFORMASI, 2022)
Business Model Canvas (BMC) is a business model with nine blocks that are used to plan a business model into a strong business strategy to be able to compete in the market. This research was conducted to plan a business model for the start-up "FEME.ID" using the Business Model Canvas method. "FEME.ID" was formed based on the problems that exist in society today, such as the stunting rate in Indonesia still reaching 24.4 percent, based on a survey conducted in July and August 2021 in 11 countries and attended by 5,496 respondents aged over 18 years. . 63% of consumers in Indonesia say that their current physical health is less than ideal, so there is a need for a platform that can be used to conduct nutrition consultations at a cost that is affordable for all. The method used in this research is descriptive method and qualitative method and primary data collection using a questionnaire. This research resulted in the planning of nine business model blocks on the start-up "FEME.ID" with the Business Model Canvas method. These nine BMC blocks form a complete business model and can be used as a business strategy to be competitive.